THE USE OF COMIC AS MEDIA IN TEACHING SPEAKING OF NARRATIVE TEXT FOR THE EIGHTH GRADERS OF JUNIOR HIGH SCHOOL - Ratih Ayu Puspitasari; Christina I.T. Panggabean (FKIP Unirow Tuban, 2016)
Speaking is one of the language skills that should be learnt by the students in studying English as a foreign language. Teachers should be creative to motivate their students with a unique and fun technique in learning. Therefore, the use of comic as a media in the class is one of the techniques that could stimulate students’ imagination to create a good story, especially used in retelling narrative text. The aims of the research are to describe how the teacher applies the use of comic and to know the students’ responses toward the use of comic in speaking narrative text. The research applies descriptive qualitative. The subject of the study were the teacher and the eighth grade students of SMPN 3 Tuban. The researcher collected the data through observation and interview. The researcher observed the condition and activities of using comic in learning narrative text in the class. After the observation the researcher interviewed some students about the use of comic as a media. They stated that learning by media such as comic was fun. They could increase their confidence when trying to retell the story in sequences by their comic and also practice their speaking well. From the data, it was found that using comic as a media is effective in teaching speaking narrative text because the teacher could know the students’ comprehension, build their imagination and creativity, and make the students enjoy the activity of speaking in narrative text. Moreover the students’ ability in speaking became better after the implementation of using comic as a media because they could retell the story by their own comic in front of other students fluently.